Direct Measures of Intergenerational Income Mobility for Australia - Chelsea Murray; Robert Clark; Silvia Mendolia; Peter Siminski (Institute of Labor Economics (IZA), 2017)
We present the first Australian estimates of intergenerational mobility that draw on direct observations of income from two generations. Using panel data for three birth cohorts of young adults from the Household, Income and Labour Dynamics Australia survey, the estimated intergenerational income elasticity is 0.28. Correcting for attenuation bias raises this to 0.41. We estimate the rank correlation to be 0.27. We show that Australia has greater mobility than the US and this is not sensitive to methodological choices. We also show that spousal selection and family structure may be important determinants of income persistence across generations.
Keywords: J62; 330; intergenerational mobility; Australia; HILDA